Economists, scientific communities, and pandemics: An exploratory study of Brazil (1918-2020) - Mauro Boianovsky (EconomiA, 2021)
The paper investigates historical aspects of the formation of the scientific community of economists in Brazil, taking the current research effort about the economics of Covid-19 as a starting-point of the narrative. The transnational character of science in general and economics in particular is highlighted. The historical trajectory of economics in Brazil is compared to other sciences', with attention to patronage and immigration. Economic debates surrounding the Spanish Flu outbreak in Brazil in 1918 are examined as an example of the working of the pre-scientific economic community in the country. Finally, some conclusions are drawn concerning the history of modern economic science in Brazil, with emphasis on the role of a couple of remarkably influential economists.
Keywords: B20; B41; I10; 330; Economists; Scientific communities; Pandemics; Brazil; Immigration